Data balance sheet in OP Financial Group - Ylinen, Mika; Järvenpää, Marko; Myllymäki, Antti (Routledge, 2022)
We use a qualitative case study research approach in Finland's largest financial services group to explore the design and use of a data balance sheet—a new and innovative form of corporate voluntary disclosure reporting. Data has become a key element for the banking industry as digitalization has created totally new business models and revolutionized traditional operating practices. In this study, we explore how OP Financial Group uses a data balance sheet to illustrate the importance of data in strategic management as well as its responsible processing and utilization. We analyze the use of the data balance sheet by the applying the lens of data monetization literature. Our findings reveal that all four main steps of data value chain—data generation, collection, analysis, and exchange—were clearly observable in OP Financial Group's Data Balance Sheet model. In addition, we observed several routes of data monetization, including building high analytical capability based on mathematical and business analytical knowledge, creating high technical data infrastructure, and applying predictive and statistical analysis. We argue that the exploitation of the data balance sheet approach will increase in the future, especially among data-intensive companies in the finance and banking industries. Data management will be one of the most important components alongside environmental, social, and governance reporting as owners, customers, and other stakeholders are increasingly requiring more transparency about value creation and the responsible use of data and artificial intelligence. This development calls for further research on data measurement and disclosure.
Keywords: cooperative banking; data analytics; data balance sheet; data monetization; digitalization; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|